PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV UPT SD NEGERI 006 SOSOR GONTING - Lusito Sihite; Rumiris Lumban Gaol; Ester Julinda Simarmata; Paska Sriulina Tarigan; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes of class IV IPAS students of SD Negeri 006 Sosorgonting in the 2024/2025 Academic Year as seen from the results of daily test scores. This type of research is quantitative research using the one group pretest posttest design method. The type of sample used is purposive sampling. The research sample used was class IVB students totaling 30 students. To determine the initial abilities of students, the study conducted a Pretest with an average score of 54.4 which is included in the less category. The results of the Pretest have increased from the results of the Posttest given previously with an average student score reaching 75.06 with a good category. It can be said that the level of success of student learning outcomes using the Jigsaw type cooperative model has increased and has an effect with a strong category as evidenced by the results of the correlation coefficient test calculation obtained the results of r_count ≥ r_table with a result of 0.778 ≥ 0.361. Furthermore, the hypothesis test that compares the value of t_count ≥ t_table. The t_count value is obtained = 6.552 while t_table = 1.697. Because t_count ≥ t_table (6.552 ≥ 1.697) then H_a is accepted and H_o is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the Jigsaw type cooperative learning model on learning outcomes in the subject of science for grade IV at SD Negeri 006 Sosorgonting in the 2024/2025 academic year.